2016
DOI: 10.2147/opth.s102130
|View full text |Cite
|
Sign up to set email alerts
|

Visual field defects and changes in macular retinal ganglion cell complex thickness in eyes with intrachoroidal cavitation are similar to those in early glaucoma

Abstract: Background/aimsTo examine the characteristics of visual field defects and optical coherence tomography (OCT) findings in eyes with intrachoroidal cavitation (ICC) and investigate the similarities between these results and glaucomatous changes.MethodsWe retrospectively analyzed patients diagnosed with ICC based on peripapillary radial cross-sectional scans performed with OCT. Visual field was measured with the Humphrey automated visual field analyzer SITA standard central 24-2 program, and macular ganglion cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…reported that the deformation of the sclera can cause biomechanical stress in the area of a PICC that can ultimately lead to PICC and nerve fibre defects in the retina. Okuma et al . suggested that PICC may be a significant risk factor for RNFL defects and glaucomatous visual field defects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…reported that the deformation of the sclera can cause biomechanical stress in the area of a PICC that can ultimately lead to PICC and nerve fibre defects in the retina. Okuma et al . suggested that PICC may be a significant risk factor for RNFL defects and glaucomatous visual field defects.…”
Section: Discussionmentioning
confidence: 99%
“…Shimada et al . and Okuma et al . used a visual field test in highly myopic PICC eyes and observed that there was a significantly higher incidence of glaucomatous visual field defects in highly myopic eyes with PICC than in those without.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,[13][14][15] Moreover, the dura 38 applies higher stress in its inner part, mechanically overloading 39 the lamina cribrosa which is the main site 42 of ON damage in glaucoma. This could explain some of the visual field defects found in PICC 1,43 as well as the high prevalence of glaucoma in myopic eyes. 44 Interestingly and supporting this hypothesis, strong adduction-induced strains on (peri)papillary structures have recently been demonstrated in glaucoma 19,45,46 and may therefore explain the pressure-independent component of visual field defects in glaucoma.…”
mentioning
confidence: 95%